In vitro and ex vivo immunomodulatory effects of human placental mesenchymal stem cells in hidradenitis suppurativa - Jariene, Vaiva; Valiukevicius, Paulius; Insodaite, Ruta; Janonyte, Ugne; Maciulaitis, Romaldas; Maciulaitis, Justinas; Vitkauskiene, Astra; Zemaite, Evelina; Zouboulis, Christos C.; Valiukeviciene, Skaidra (Frontiers in Immunology, 2025)
BackgroundHidradenitis suppurativa is a chronic inflammatory skin disease marked by immune dysregulation and elevated pro-inflammatory cytokines. While biologics like adalimumab target specific pathways, their limited efficacy highlights the need for broader immunomodulatory treatments. Mesenchymal stem/stromal cells (MSCs) have shown promise due to their immunosuppressive properties and ability to modulate both innate and adaptive immunity. This study investigates the effects of naïve (n-MSCs) and cytokine-preactivated (a-MSCs) placental MSCs on the immune responses in HS.MethodsMSCs were isolated from healthy term placentas and either used naïvely or preactivated with IFN-γ and TNF-α. Peripheral blood mononuclear cells (PBMCs) from HS patients (n=3) and healthy donors (n=3) were co-cultured with n-MSCs, a-MSCs, or adalimumab. Additionally, lesional, perilesional, and healthy 4 mm in diameter skin punch biopsies from 10 HS patients and 3 controls were cultured in a transwell system with the same interventions. Flow cytometry assessed lymphocytes proliferation and T cell subsets while Luminex assays measured cytokine levels.ResultsBoth n-MSCs and a-MSCs significantly inhibited lymphocytes proliferation and shifted T cell populations, increasing CD4+ and decreasing CD8+ T cells. The a-MSCs notably reduced IL-17A and IFN-γ in PBMC co-cultures; n-MSCs had partial effects. HS skin explants exhibited elevated IL-1β, IL-10, and IL-17A compared to healthy skin. The n-MSCs markedly reduced all three cytokines in lesional and perilesional tissues. Moreover, a-MSCs selectively increased IL-10 in lesional skin.ConclusionPlacental MSCs, especially in their naïve form, demonstrate potent immunomodulatory effects by reducing pro-inflammatory cytokines and altering T cell dynamics in HS. Compared to adalimumab, MSCs offer a broader immunoregulatory profile, suggesting their potential as a multitarget therapy for HS. These findings support further clinical investigation of MSC-based treatments in managing this complex disease.